Implementasi Kebijakan Perlindungan dan Pemberdayaan Petani Terhadap Penentuan Kawasan Prioritas Pertanian di Kabupaten Badung - Astuti, Made Prajaditha; Bandiyah, Bandiyah; Jayanthi Mertha, A.A Sagung Mirah Mahaswari (Jurnal Nawala Politika, 2021)
ABSTRACT The research is about the problem of optimizing the development of farmers protection and empowerment which tend to be more used in the North Badung and indicates a political interpretation of the central rice farmers. Research objectives include: (1). Track the social conditions of content and context about politic of the implementation of farmers protection and empowerment policies.The theory used is the theory of public policy implementation of Merille S. Grindle and rational choice theory using a qualitative approach to obtaining data. The findings suggest that implementation of the safeguard and empowerment of farmers has not been optimal because of being more affected by the political environment of the influence of the actors decisions. The regions and high priority commodities in the northern Badung region specialize in horticultural commodity which is generating the economic advantage of agro-tourism. Keywords:political actors, implementation of farmers protection and empowerment policies, priority region, farmers.